Recommendations for improving accessibility of digital health interventions for cardiometabolic disease for ethnically diverse populations - Mel Ramasawmy; Nushrat Khan; David Sunkersing; Madiha Sajid; Shivali H Modha; Manoj Mistry; Wasim Hanif; Fiona Stevenson; Kiran Patel; Kamlesh Khunti; Paramjit Gill; Lydia Poole; et al. (Digital Health)
Digital health interventions (DHIs), such as apps, websites and wearables, are being presented as solutions or enablers to manage the burden of cardiometabolic disease in healthcare. However, the potential benefits of DHIs may not be reaching the most in-need populations, who may face intersecting barriers to accessing health services and digital solutions. The Digital Interventions for South Asians in Cardiometabolic Disease (DISC) study used a mixed-method approach to focus on people of a South Asian background, a high-risk group for cardiometabolic disease. A one-day workshop was held in May 2023 with key stakeholders, including people with lived experience, health professionals, technology innovators and policymakers ( n  = 34), to develop recommendations arising from the DISC study findings. Discussions covered four areas: actions to support individuals to access and benefit from DHIs; translating learning about inclusive design into practice; the role of regulation and evaluation to improve inclusivity of DHIs used within the health service; and improving quality of data collection and use to reduce inequalities related to digital health and cardiometabolic disease. Our recommendations align with recent national strategies and provide specific examples of actions that can be taken to address digital inequalities for ethnic minority populations.